Effect of scale on surface runoff processes - Barbancho, A. C.; Schnabel, S.; Bolinches, C. (CADERNOS DO LABORATORIO XEOLOXICO DE LAXE 21, 1996)
In a small catchment under the so-called dehesa landuse system, the production of surface runoff is investigated at different scales. This includes experiments with simulated rainfall at micro-plots, event-based measurements of overland flow at 17 open plots and 1 closed plot, and discharge production of the catchment and subcatchment. The runoff coefficients of the considered scales form two groups, with low values for the catchment and sub-catchment and high values for the microplots and hillslope plots. The results show that large part of runoff produced at the slopes is infiltrated afterwards at colluvial sites and the valley floors. Furthermore, they indicate the importance of studying at various scales in order to understand the hydrological processes operating in catchments.
The following values have no corresponding Zotero field: periodical: CADERNOS DO LABORATORIO XEOLOXICO DE LAXE 21 pub-location: O CASTRO DE SAMOEDO, 15168 SADA, LA CORUNA, SPAIN
Keywords: ecosystem dehesa; scale; soil erosion; surface runoff